Optimizing the wash time of the washing machine using several types of fuzzy numbers (Journal of Bangladesh Academy of Sciences, 2021)
In this paper we used various fuzzy numbers to calculate wash time for washing machines and provided various decisions after comparison among them. Again, this paper shows the importance of fuzzy logic control-based washing machine to get an appropriate wash time for the degree of dirt and the quantity of grease present on the clothes. This method is predicated on a fuzzy inference system. A fuzzy inference system using the Mamdani controller type is illustrated in this paper. From the utilization of fuzzy logic control, the machine can respond in several conditions. The simulation was done by MATLAB programming language.J. Bangladesh Acad. Sci. 45(1); 105-116: June 2021